2008
DOI: 10.1007/s11224-008-9395-7
|View full text |Cite
|
Sign up to set email alerts
|

Quantum chemical analysis of the energetics of the anti and gauche conformers of ethanol

Abstract: Ethanol displays two stable conformers, the classic anti (or trans) form and a gauche conformation in which the hydroxyl hydrogen points toward one of the methyl hydrogens. Surprisingly, the two forms have nearly equal energies, and in the vapor phase the gauche form predominates because of its twofold degeneracy. An analysis of the energetics of these conformers based on natural bond orbital analysis helps to explain the apparently anomalous near degeneracy of these conformers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
24
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 21 publications
2
24
0
Order By: Relevance
“…In these cases, descriptors for the dominant conformer were used in the regressions. For example, for ethanol it is known that the anti and gauche forms are nearly equivalent in energy22; since the qauche form is doubly degenerate this form prevails and has been used in calculating the descriptors for ethanol, trifluoroethanol, 2‐propanol, and hexafluoro‐2‐propanol (in some cases it is possible to measure the energy differences between the conformers, e. g., Pratt and coworkers have measured the OH rotamer energy differences in naphthols23 and some substituted benzenes24 using high‐resolution gas‐phase measurements). The structures of the azoles studied are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, descriptors for the dominant conformer were used in the regressions. For example, for ethanol it is known that the anti and gauche forms are nearly equivalent in energy22; since the qauche form is doubly degenerate this form prevails and has been used in calculating the descriptors for ethanol, trifluoroethanol, 2‐propanol, and hexafluoro‐2‐propanol (in some cases it is possible to measure the energy differences between the conformers, e. g., Pratt and coworkers have measured the OH rotamer energy differences in naphthols23 and some substituted benzenes24 using high‐resolution gas‐phase measurements). The structures of the azoles studied are shown in Figure 1.…”
Section: Methodsmentioning
confidence: 99%
“…The NBO (natural bond orbital) analysis of the energetics of the two conformers revealed that they have closely comparable energies due to compensatory effects. [21] Thus, the authors demonstrate how the structures are stabilized during internal rotation by charge transfer from the oxygen lone pairs on the one hand, into the (methyl) C-H bonds (anti) and into the C-C bonds (gauche), on the other. First of all this applies for the conditions in the vapor phase, where the gauche form is slightly predominant.…”
Section: Crystal Structuresmentioning
confidence: 95%
“…[20] On closer examination this seems quite plausible because the classic anti conformation would conflict with the neighboring amino groups generating hydrogen distances shorter than H-H = 1.8 Å. In this context, "the apparently anomalous near degeneracy of these conformers" [21] is worth mentioning. The NBO (natural bond orbital) analysis of the energetics of the two conformers revealed that they have closely comparable energies due to compensatory effects.…”
Section: Crystal Structuresmentioning
confidence: 99%
“…Despite many theoretical studies, the relative stability of the conformers strongly depended on the method and the size of the basis set: gauche is slightly more stable by MP2/6-3111G ⁄⁄ [1], whereas anti is more stable by 0.52 and 0.42 kJ mol À1 , respectively by MP4/6-31+G ⁄⁄ [2] and B3LYP/6-311++G ⁄⁄ [3]. As summarized in the latest study [4], the results obtained by HF, B3LYP, MP2, MP4, CCSD(T) using 6-31G ⁄ , 6-311+G ⁄ , 6-311G ⁄⁄ , 6-311++G ⁄⁄ , etc. have led to the conclusion that the energy difference between the conformers ranges between À1.18 and +1.33 kJ mol À1 .…”
Section: Introductionmentioning
confidence: 99%